O papel da escola no processo de formação de sujeitos sociais em situação prisional - Silva, Aline Porto da [UNESP] (2015)
Since the beginning of the first prisions, they were proposed to solely for custody of offenders while waiting for capital punishment. With the evolution of the society, also evolves to the form of the punishment of convicts, going to be adopted custodial sentences instead of tortured bodies, then came up a greater concern with the most suitable sites for this new purpose. This study aim to reflect and analyze the relationship between education and rehabilitation in the Brazilian criminal justice system, aiming to give the efficiency of these programs in the country and the emergence of the first forms of punishment and deprivation of liberty, presupposing the role that education presents in the social reintegration process, in a situation of deprivation of liberty and the existing public policies. Characterize and show the attempts made by the state of São Paulo in accomplishing new models of prisons, which since 2000 are called resocialization centers representing this new structure and proposed social work in relation to so-called traditional prisons